2016
DOI: 10.1080/21645515.2016.1245250
|View full text |Cite
|
Sign up to set email alerts
|

Achievements and challenges for the use of killed oral cholera vaccines in the global stockpile era

Abstract: Cholera remains an important but neglected public health threat, affecting the health of the poorest populations and imposing substantial costs on public health systems. Cholera can be eliminated where access to clean water, sanitation, and satisfactory hygiene practices are sustained, but major improvements in infrastructure continue to be a distant goal. New developments and trends of cholera disease burden, the creation of affordable oral cholera vaccines (OCVs) for use in developing countries, as well as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 51 publications
0
21
0
1
Order By: Relevance
“…outbreak response or humanitarian crisis) is managed by the International Coordinating Group (ICG), composed by Médecins Sans Frontières (MSF), the International Federation of Red Cross/Crescent (IFRC), Unicef, and the WHO; while the allocation of OCV in non-emergency (i.e. vaccination in cholera endemic “hotspots”) is coordinated by the Global Task Force on Cholera Control (GTFCC), a WHO coordinated network of partners active in controlling cholera [ 9 ]. According to the last WHO’s report, since creation of the stockpile, as of April 2017, almost 8 million doses of OCV have been shipped for the implementation of more than 40 OCV vaccination campaigns in 14 countries [ 10 ] including Cameroon, Democratic Republic of the Congo, Ethiopia, Guinea, Haïti, Iraq, Malawi, Niger, South Sudan and Zambia [ 11 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…outbreak response or humanitarian crisis) is managed by the International Coordinating Group (ICG), composed by Médecins Sans Frontières (MSF), the International Federation of Red Cross/Crescent (IFRC), Unicef, and the WHO; while the allocation of OCV in non-emergency (i.e. vaccination in cholera endemic “hotspots”) is coordinated by the Global Task Force on Cholera Control (GTFCC), a WHO coordinated network of partners active in controlling cholera [ 9 ]. According to the last WHO’s report, since creation of the stockpile, as of April 2017, almost 8 million doses of OCV have been shipped for the implementation of more than 40 OCV vaccination campaigns in 14 countries [ 10 ] including Cameroon, Democratic Republic of the Congo, Ethiopia, Guinea, Haïti, Iraq, Malawi, Niger, South Sudan and Zambia [ 11 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, there has been an increased enthusiasm in its use for the prevention of cholera. A review from the WHO reported that up to 35 OCV campaigns were conducted between July 2013 to July 2016 in response to emergency and endemic contexts in various settings [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The vaccine has most often been given in two doses, 14 days apart, as recommended by the manufacturers. 9 Yet giving a second dose of OCV on schedule can be challenging during crisis situations. Furthermore, multiple competing demands on the global stockpile mean that, at times, officials might have to decide if they should vaccinate a population without guarantee of the availability of the second tranche of doses.…”
Section: Cholera Control: One Dose At a Timementioning
confidence: 99%